Comparative Analysis of Student Learning Outcomes of Conventional Learning with Genetic Intelligence-Based Learning - Kibtiyah, Asriana; Rofi’ah, Siti; Umam, Khoirul; Bahrodin, Ariga; Idawati, Khoirotul; Supratno, Haris (LP2M STIT Palapa Nusantara, 2025)
This study compares the learning outcomes between two groups from equivalent schools. One group underwent an assessment to identify the genetic intelligence types of both teachers and students. Teachers in this experimental group, having become familiar with their own and their students' genetic intelligence types, received additional training tailored to these intelligence types. The results indicated a significant difference in learning outcomes between the experimental and control groups, as evidenced by an Independent Samples t-Test yielding a two-tailed p-value of 0.001 (p < 0.05). Furthermore, the experimental group's average post-test score was 73, compared to 69.62 in the control group.